A multi-scale methodology of turbine blade surface recovery based on photometric stereo through fast calibrations. (March 2022) - Ma, Long; Liu, Yuzhe; Liu, Jirui; Pei, Xin; Sun, Fengming; Shi, Lei; Fang, Shaobo
Highlights: A novel multi-scale measurement methodology for turbine blade is proposed to retrieve different geometrical features of turbine surface in different scales. A LED calibration algorithm is discussed by a single shot per each light source to ensure a fast transition of scales, and a multi-scale calibration target is designed for turbine blade measurement. A high accuracy surface recovery method based on photometric stereo is improved where the initial depth value can be directly estimated from the LED calibration, and enables the iteration approach to start automatically. Abstract: This paper proposed a multi-scale measurement methodology for turbine blade, which is able to evaluate the geometrical features of turbine surface in different scales. A turbine blade measurement system is designed by using LED illuminators in this work. To ensure the efficiency and the accuracy of our system during the scale transition, a fast light source calibration method is introduced with a special designed calibration target, where with only one camera snapshot, the position and the orientation of a LED can be calibrated precisely and simultaneously. A surface reconstruction algorithm via iteration is improved by analyzing the LED radiant intensity distribution. The simulation is carried out with a synthetic hyperboloid structure, where the root mean square error (RMSE) of rebuilding is lower than 1.7 µm, and the mean angular error(MAE) of normal estimation is 0.5°. System calibration is performed by using a USAF 1951 calibration target with 3 different scales with the minimum deviation below 4 µm. Experiments are implemented on the concave and the tenon of a turbine blade from civil aero engine, where the profile, the size of the cooling hole and the roughness are retrieved successfully in different scales, which shows the great potential of the proposed methodology in blade inspection applications.